Vpliv plazemske obdelave površine lesa na lepljenje bukovine s poliuretanskim lepilom - Capuder, Martin (Les (Ljubljana), 2024)
The study investigated the effects of plasma surface treatment on bonding beech wood with structural one-component polyurethane adhesive. The wood used included European beech (Fagus sylvatica L.) without discolouration and red-heart beech, and the efficiency of the adhesive joints was evaluated by testing shear strength and delamination according to the SIST EN 14080:2013 standard. The results showed that plasma treatment improved the wettability of the surface but did not contribute to enhancing the quality of the adhesive joints. In the case of red-heart beech, a higher degree of wood failure was observed, while the shear strengths of the adhesive joints were lower. Using polyurethane adhesive for bonding beech wood did not meet the standard requirements for adhesive joint delamination. The study did not show significant differences in bonding between beech wood without discolouration and red-heart beech.
Keywords: European beech; Fagus sylvatica; konstrukcijsko lepljenje; les; navadna bukev; plasma surface treatment; plazemska obdelava površine; poliuretansko lepilo; polyurethane adhesive; rdeče srce; red heart; structural bonding; wood